(untitled) (Hematology Meeting Reports, 2009)
Belinostat (PXD101) is a hydroxamate pan HDAC inhibitor which demonstrates broad antineoplastic activity in vitro and in vivo. Phase I studies have shown that belinostat is well-tolerated and has had activity in T-cell malignancies.